NALISIS PERAN KOPERASI MERAH PUTIH BERBASIS MODAL SOSIAL LOKAL DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA MEDAN KRIO DI KABUPATEN DELI SERDANG - Reva Parapat; Imanuddin Husayn Sormin; Puan Adea Zahwa; Ruth Angel Avrillia Hutagalung; Rifky Hasyim Ananta; Shofwan Sasri Azhari; Parlaungan Gabriel Siahaan (STKIP Subang, 2026)
This study aims to analyze the role of the Red and White Cooperative based on local social capital in improving the welfare of the community in Medan Krio Village, Sunggal District, Deli Serdang Regency. The study focuses on three dimensions of social capital proposed by Putnam, namely trust, social networks, and social norms. A qualitative approach with a descriptive method was employed. Primary data were collected through participatory observation and in-depth interviews with the Village Secretary, cooperative administrators, and cooperative members. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that trust among members is strengthened through transparent organizational management, particularly in the presentation of financial reports during Annual Members Meetings and through active communication using digital media. Social networks are utilized to expand economic cooperation, both vertically through partnerships with institutions and strategic commodity distributors, and horizontally through support for local micro-enterprises. Social norms are reflected in collective responsibility and community participation, particularly in the management of self-funded cooperative capital. The integration of these three dimensions of social capital contributes to improved economic access, strengthened business activities, and greater operational efficiency among micro enterprises. Nevertheless, the cooperative continues to face challenges related to limited technological utilization and low participation of younger generations in organizational activities. Therefore, strengthening digital capacity and implementing more participatory engagement strategies are necessary to support the sustainable development of the cooperative